2016
DOI: 10.1016/j.bbr.2016.03.035
|View full text |Cite
|
Sign up to set email alerts
|

A murine model of peripheral irradiation-induced fatigue

Abstract: Purpose Fatigue is the most ubiquitous side effect of cancer treatment, but its etiology remains elusive. Further investigations into cancer-related fatigue pathobiology necessitate the expanded use of animal models. This study describes the development of a murine model of radiation-induced fatigue. Methods Voluntary wheel running activity measured fatigue in 5–8 week-old, male C57BL/6 mice before and after γ irradiation totaling 2400 cGy (3 consecutive days × 800 cGy daily fractionated doses) to the lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 46 publications
3
28
1
Order By: Relevance
“…Peripheral irradiation of mice causes a decrease in voluntary wheel running [20, 33] and, in this study, showed a similar fatigue-like effect in the TFT. This provides further validation that this mouse model induces fatigue and establishes a foundation for future studies to use either or both assays to measure fatigue-like behavior in mice.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…Peripheral irradiation of mice causes a decrease in voluntary wheel running [20, 33] and, in this study, showed a similar fatigue-like effect in the TFT. This provides further validation that this mouse model induces fatigue and establishes a foundation for future studies to use either or both assays to measure fatigue-like behavior in mice.…”
Section: Discussionsupporting
confidence: 69%
“…Female C57BL/6 mice were used for chemotherapy-induced fatigue experiments, which used 5-FU to induce fatigue, as this strain and sex was used to establish the TFT [30] and in other studies using 5-FU [19, 31]. Male C57BL/6 mice were used for the radiation-induced fatigue experiment as this strain and sex was used to establish this model [20]. Balb/c mice were used for the colon 26 carcinoma (C26) model as cells used to produce tumors were originally derived from this strain [24].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations